EU REPower Plan 2022: Reducing Russian Energy Dependence Through Renewables and Energy Security Framework - Safdar Ali, Ayisha; Mirza, Ayesha (Journal of Professional Research in Social Sciences, 2025)
The REPowerEU initiative (2022–2025) illustrates a strategic transition in the European Union’s energy policy, centered on three pillars: energy efficiency, clean energy expansion, and diversification of energy imports. The research highlights the progress in decreasing reliance on Russian fossil fuels and advancing renewable energy deployment. Significant achievements include a marked decline in Russian energy imports and a surge in solar and wind capacity across the EU. Germany’s rapid solar rollout underlines effective implementation, while Eastern European states face challenges due to underdeveloped LNG infrastructure, revealing disparities in national readiness and investment. Despite these improvements, the initiative faces structural obstacles such as delayed permitting processes and uneven implementation across member states. REPowerEU has also influenced the EU’s geopolitical orientation, reinforcing energy ties with the U.S. and Norway. However, new dependencies particularly on hydrogen and critical raw materials pose long-term strategic risks. Addressing these issues requires streamlined regulatory frameworks, targeted funding to alleviate energy poverty, and proactive measures to manage emerging vulnerabilities. The research presents a subtle insight into REPowerEU’s potential to reshape the EU’s energy landscape, highlighting the momentum gained and the enduring complexities of achieving a sustainable and resilient energy future.